The implications of artificial substrate material type for sessile fouling communities along the South African east coast - Matikinca, Phikolomzi; Zondi, Vuyiswa (Frontiers in Marine Science, 2025)
IntroductionThe growing blue economy and rapid development and urbanisation of coastal areas drive an increase in marine infrastructures. These structures are built with artificial materials and the submerged parts thereof become substrates for colonisation by fouling biota which are often dominated by invasive alien species. However, knowledge on the ecological implications of artificial substrate material for marine biota remains limited, with a notable research gap with respect to Africa.MethodsThis field study assessed how artificial substrate material type might influence sessile fouling communities along the South African east coast. Fiberglass, High-Density Polyethylene (HDPE) and Polyvinyl Chloride (PVC) panels were used as artificial substrates for biofouling community settlement over a period of three months.ResultsDifferences in artificial substrate material type influenced sessile fouling community structure, with fiberglass panels showing a dominant effect than the other two types of materials. Fiberglass panels also supported higher species diversity and percentage cover than the HDPE and PVC panels. Notably, no significant effect of species status (invasive and native) was detected on overall percentage cover.DiscussionThese results highlight the dominant influence of fiberglass materials on sessile assemblages. Overall, this study suggests that the type of material used in artificial marine structures may have ecological implications and therefore, should be included as an important consideration in material selection criteria.